The Students Perspective of Practice Speaking for Social Intercultural Communication During Online Learning - Muhammad Ilyas; Feni Febriana; Tisa Anggraini; Widya Efrialis (Journal of English Language and Education, 2023)
This action research aims at knowing the 4th-semester student's perspective for practicing the subject in the 3rd semester which is Speaking for Social Intercultural communication. The study, which uses a survey method based on questionnaire data and the case study method as a research design, was carried out on 28 students of English Language Education at the Islamic University of Riau in the 4th semester. The research took place over 1 week and the questionnaire consisted of 31 questions from five indicators of online learning and was shared via WhatsApp Group. The data presented that the dominant percentage of total students gave a positive perspective for practicing speaking in online learning.